1995
DOI: 10.1016/1074-7613(95)90144-2
|View full text |Cite
|
Sign up to set email alerts
|

A signaling pathway coupled to T cell receptor ligation by MMTV superantigen leading to transient activation and programmed cell death

Abstract: Stimulation of T cells by retroviral and bacterial super-antigens is followed by specific T cell elimination, in contrast with stimulation of T cells by peptide, which is usually associated with clonal expansion. We show here that this differential response phenotype is apparent at the level of individual T cell clones following TCR ligation with peptide or MTV antigen. We exploited selective coupling of apoptosis to TCR ligation by MTV7 to examine some of the intracellular biochemical events that underlie thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
1
28
1
1
Order By: Relevance
“…We postulate that once the conditions for suppression have been established in vivo, subsequent antigenic restimulation in vitro promotes further IFN-␥ production, stimulating small numbers of Gr-1 ϩ cells in the enriched T cell cultures to produce a combination of RNI and ROI. Our data suggest that RNI and ROI directly cause activated or responding CD4 T cells to undergo apoptosis, as has been suggested in other models (20,21,33,34). This possibility will be further investigated in future studies.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We postulate that once the conditions for suppression have been established in vivo, subsequent antigenic restimulation in vitro promotes further IFN-␥ production, stimulating small numbers of Gr-1 ϩ cells in the enriched T cell cultures to produce a combination of RNI and ROI. Our data suggest that RNI and ROI directly cause activated or responding CD4 T cells to undergo apoptosis, as has been suggested in other models (20,21,33,34). This possibility will be further investigated in future studies.…”
Section: Discussionsupporting
confidence: 61%
“…More recently, a mimetic of SOD was used to show that low doses of injected SEA can induce a superoxidemediated mechanism of cell death in T cells from SAg-treated mice (21). This study did not show in vivo data; however, an earlier study showed that NAC slightly enhanced T cell survival in mice stimulated with a mouse mammary tumor virus-derived SAg (20). The origin of the ROI was not investigated in either of these studies.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The induction of various oxidoreductase genes by osteopontin, found in the microarray analysis, is consistent with these functions. Apoptosis frequently involves the generation of and signal transduction by free radicals (Weber et al, 1995). Anchorage independence in soft agar largely reflects resistance to a form of apoptosis referred to as anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ROS play a pivotal role in numerous signaling pathways in physiologic and pathophysiologic settings. In T cells, several studies have suggested that T cell activation stimulates ROS generation (5)(6)(7).…”
mentioning
confidence: 99%